Procyanidin C1 from Viola odorata L. inhibits Na+,K+-ATPase - Tomas Heger; Marek Zatloukal; Martin Kubala; Miroslav Strnad; Jiri Gruz (Scientific Reports, 2022)
Abstract Members of the Viola genus play important roles in traditional Asian herbal medicine. This study investigates the ability of Viola odorata L. extracts to inhibit Na+,K+-ATPase, an essential animal enzyme responsible for membrane potential maintenance. The root extract of V. odorata strongly inhibited Na+,K+-ATPase, while leaf and seeds extracts were basically inactive. A UHPLC-QTOF-MS/MS metabolomic approach was used to identify the chemical principle of the root extract’s activity, resulting in the detection of 35,292 features. Candidate active compounds were selected by correlating feature area with inhibitory activity in 14 isolated fractions. This yielded a set of 15 candidate compounds, of which 14 were preliminarily identified as procyanidins. Commercially available procyanidins (B1, B2, B3 and C1) were therefore purchased and their ability to inhibit Na+,K+-ATPase was investigated. Dimeric procyanidins B1, B2 and B3 were found to be inactive, but the trimeric procyanidin C1 strongly inhibited Na+,K+-ATPase with an IC50 of 4.5 µM. This newly discovered inhibitor was docked into crystal structures mimicking the Na3E1∼P·ADP and K2E2·Pi states to identify potential interaction sites within Na+,K+-ATPase. Possible binding mechanisms and the principle responsible for the observed root extract activity are discussed.